Indigenous Law and the Politics of Kincentricity and Orality - Kearney, Amanda; Bradley, John; Dodd, Vincent; Norman a-Marrngawi, Dinah; Timothy a-Muluwamara, Mavis; Dimanyurru, Graham Friday; a-Karrakayny, Annie (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This Palgrave Pivot strives to recount and understand Indigenous Law, as set within a remote community in northern Australia. It pays close attention to the realpolitik and high-level political functioning of Indigenous Laws, which inspires a discussion of how this Law models the relational, influences governance and emplaces people in an ordered kincentric lifeworld. The book argues that Indigenous Law can be examined for the ways in which it is a deliberate, stabilizing and powerful force to maintain communal order in relation to Country, a counter framing to popular and 'soft law or soft power asset' visions of such Laws often held in the national and international imaginary. It is the latter which too often renders this knowledge esoteric and relinquishes it to a category of lore or folklore. Amanda Kearney is a Professorial Fellow in the School of Culture and Communication, University of Melbourne, Victoria, Australia. John Bradley is Associate Professor in the Monash Indigenous Studies Centre, Monash University and Director of the Wunungu Awara Indigenous Cultural Animation Program, Australia. Vincent Dodd is a PhD candidate in the Monash Indigenous Studies Centre, Monash University, Australia. Dinah Norman a-Marrngawi is a Yanyuwa Community Elder, li-Wirdiwalangu Elders Group, Northern Territory, Australia. Mavis Timothy a-Muluwamara is a Yanyuwa Community Elder, li-Wirdiwalangu Elders Group, Northern Territory, Australia. Graham Friday Dimanyurru was a Yanyuwa Community Elder, li-Wirdiwalangu Elders Group, Northern Territory, Australia. Annie a-Karrakayny was a Yanyuwa Community Elder, li-Wirdiwalangu Elders Group, Northern Territory, Australia.